2015
DOI: 10.1016/j.humimm.2015.07.235
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of next generation sequence-based and sequence specific oligonucleotide probe-based HLA-DRB1 genotyping

Abstract: Next generation sequencing (NGS) of clonally amplified DNA, using Roche 454 technology, was used to genotype HLA-DRB1, DRB3, DRB4, and DRB5 loci (exon 2 only) from a set of 993 samples from newborns with maternally-reported African American ancestry. DRB1 exon 2 was genotyped previously on the same sample set using sequence-specific oligonucleotide probe (SSOP) technology. Comparison of the genotype calls from both methods indicated concordance of 92.3%. Some discordance was expected due to the higher resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
2
3
0
Order By: Relevance
“…A thorough validation should not only determine whether an assay performs robustly, but also identify areas of concern. Consistent with previous reports, HLA typing of DRB1/3/4/5 was the most difficult 22,24,25 (Table 2). These issues arise because of primer locations inhibiting the ability to resolve certain HLA alleles.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A thorough validation should not only determine whether an assay performs robustly, but also identify areas of concern. Consistent with previous reports, HLA typing of DRB1/3/4/5 was the most difficult 22,24,25 (Table 2). These issues arise because of primer locations inhibiting the ability to resolve certain HLA alleles.…”
Section: Discussionsupporting
confidence: 91%
“…TruSight HLA demonstrated efficient generation of long-range HLA amplicons (Figure 1) and NGS libraries that consistently generated high-quality data (Figures 2 and 3). The degree of concordance is consistent with previous reports comparing different sequencing platforms and NGS HLA assays 17,21,22 (Table 2). The costeffectiveness of HLA typing by NGS is consistent with a report by Stoddard et al 23 on the use of NGS compared to Sanger for diseases with multiple candidate genes (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…This is somewhat surprising as Lane et al [ 33 ] compare the HLA status derived from SSOP against clonally amplified DNA, using Roche 454 technology for 993 samples from newborns with maternally reported African American ancestry and found a concordance of 92.3%. However, it is consistent with Gourley et al [ 34 ], who reported typing discrepancies between 3.9% and 6.7% for HLA-A and B, respectively, based on SSOP typing of 1983 samples.…”
Section: Resultsmentioning
confidence: 99%
“…We generated a new reference panel of HLA-typed individuals in a subset of the AA data. A total of 308 subjects were genotyped for classical class II HLA alleles (HLA * DQA, HLA * DQB and HLA * DRB1) by targeted sequencing of exons 2 and 3 ( HLA-DQA and HLA-DQB ) and exon 2 ( HLA-DRB1 ) ( 17 ). These were added to the database of reference HLA genotypes for HLA imputation with the software HLA * IMPV2 ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 308 subjects were also genotyped for classical class II HLA alleles (HLA * DQA, HLA * DQB and HLA * DRB1) by targeted sequencing of exons 2 and 3 ( HLA-DQA and HLA-DQB ) and exon 2 ( HLA-DRB1 ) ( 17 ). This set included the ‘HLA reference set’ used for HLA imputation into the rest of the AA study.…”
Section: Methodsmentioning
confidence: 99%